2022
DOI: 10.20473/ijph.v17i3.2022.477-487
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Free Larvae Index and Population Density With Dengue Fever Incidence Rate

Abstract: Introduction: Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus that infects the body. Dengue is a common viral infection in warm tropical climates. The infection is caused by one of four closely related dengue viruses. The disease now plagues many countries and even more than 100 countries within the WHO, including Africa, the Americas, the Eastern Mediterranean, Southeast Asia, and the Western Pacific. The Americas, Southeast Asia, and the Western Pacific are the most severely affected r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…These results are in line with earlier research carried out in the Blitar District between 2013 and 2017, which found no correlation between the incidence rate of DHF and LFI (p=0.06) (25). On a nationwide level in Indonesia, other similar studies also showed no significant correlation between the incidence rate of DHF and LFI (p=0.42) (25). Research in the East Lombok District revealed contradictory findings; a high incidence rate of DHF was associated with a low LFI value (26).…”
Section: Pattern Of Dengue Hemorrhagic Fever (Dhf) Cases Based On Placesupporting
confidence: 92%
See 1 more Smart Citation
“…These results are in line with earlier research carried out in the Blitar District between 2013 and 2017, which found no correlation between the incidence rate of DHF and LFI (p=0.06) (25). On a nationwide level in Indonesia, other similar studies also showed no significant correlation between the incidence rate of DHF and LFI (p=0.42) (25). Research in the East Lombok District revealed contradictory findings; a high incidence rate of DHF was associated with a low LFI value (26).…”
Section: Pattern Of Dengue Hemorrhagic Fever (Dhf) Cases Based On Placesupporting
confidence: 92%
“…However, there is one circumstance in which the incidence of DHF increases as the LFI value decreases. These results are in line with earlier research carried out in the Blitar District between 2013 and 2017, which found no correlation between the incidence rate of DHF and LFI (p=0.06) (25). On a nationwide level in Indonesia, other similar studies also showed no significant correlation between the incidence rate of DHF and LFI (p=0.42) (25).…”
Section: Pattern Of Dengue Hemorrhagic Fever (Dhf) Cases Based On Placesupporting
confidence: 90%
“…Densely populated environments and their association with dengue cases are also related to the flying ability of Aedes aegypti mosquitoes as vectors, which can reach distances of less than 50 meters. This phenomenon may increase the risk of spreading DHF in densely populated environments [11].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to previous studies, higher population density was associated with a visually higher temperature-dengueran association than low population dense areas [ 33 , 55 ]. In Indonesia, Nuranisa, et al [ 56 ] noted a positive correlational association between dengue incidence and population density. These highly dense areas provide suitable conditions for vector proliferation and subsequent disease transmission [ 57 ].…”
Section: Discussionmentioning
confidence: 99%